Tribo-mechanical behaviour of aluminium-based metal matrix composite: A review. (2021) - Singh, Pratik; Gupta, Raj; Izan, Saif; Singh, Shubham; Sharma, Rajat; Dwivedi, Shashi Prakash
Abstract: Nowadays, manufacturing industries are focusing on the light weight material along with good mechanical and wear resistance properties. Aluminium and aluminium alloys are light weight material as compared to Iron. However, its strength and hardness are also lower than Iron. Strength and hardness of aluminium alloys are improved by adding the different reinforcement particles. In the present study, critical review of aluminium based composite material has been carried out to enhance the mechanical and tribological behaviour of the aluminium alloy.